Efektivitas Media Edukasi Berbasis QR Code Terhadap Peningkatan Pengetahuan Ibu Tentang ASI Eksklusif - Fitrya Ayu Anggraini (Universitas Ivet, 2026)
Achieving suboptimal exclusive breastfeeding rates remains a challenge in supporting maternal and infant health. Contributing factors include mothers insufficient awareness of the importance of exclusive breastfeeding. The use of digital technology via QR codes offers a more flexible and accessible alternative for health education. This study aimed to analyze the impact of using QR code-based educational materials on mothers' knowledge of exclusive breastfeeding in Palenca Raya. The study employed a simple experimental design with pre- and post-intervention measurements on a group of participants. Thirty mothers who met the study criteria participated in the activity. Participants' knowledge was measured using a questionnaire distributed before the education and again one week after they accessed the materials via QR codes. Due to the non-normal distribution of the data, the Wilcoxon signed-rank test was used for analysis. The results showed an increase in knowledge after the intervention, with most participants experiencing an increase in their scores on the final assessment. The difference was statistically significant (p<0.05). These results suggest that QR code-based educational materials have the potential to be used as a health promotion tool to improve mothers' knowledge of exclusive breastfeeding and to advance digital health education in primary healthcare.